Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

1 . PROVE BY ELEMENT-ARGUMENT METHOD THAT: AU(B-A)=AUB A-(AnB)=AnB c [ (AnB)UC ] c =(AUC) c U(BUC) c (AUB) c= A c nB c 2. PROVE THAT THE FOLLOWING IS TRUE: (AXB)UC=(AXB)n(AXC)

1.
PROVE BY ELEMENT-ARGUMENT METHOD THAT:
  1. AU(B-A)=AUB
  2. A-(AnB)=AnBc
  3. [(AnB)UC]c=(AUC)cU(BUC)c
  4. (AUB)c=AcnBc
2.
PROVE THAT THE FOLLOWING IS TRUE:
  1. (AXB)UC=(AXB)n(AXC)

Grade:6

1 Answers

Saurabh Koranglekar
askIITians Faculty 10341 Points
one year ago
Dear student

Please understand the concept of set theory by following the link

https://www.askiitians.com/iit-jee-algebra/set-relations-functions/set-theory/operations-on-sets/

Regards

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free